Analisis Dampak Kebijakan Penurunan Pajak Penghasilan Terhadap Pertumbuhan Ekonomi Nasional - Adam Bachtiar (Syntax Idea)
Tax has an important role, because it is the main source of state income. In Indonesia, there are various types of taxes, including income tax. The tax intensive, which is in the form of a tax reduction, is expected to increase awareness of paying tax obligations. However, everything has risks including a decrease in income tax on national economic growth. This study aims to analyze the impact of income tax reduction on national economic growth. This research uses descriptive analysis method with qualitative approach. Based on the results of the study, it is found that the impact of income tax reduction on national economic growth highlights the complexity of the interaction between taxes, income distribution, work incentives, and production. Reducing income tax in certain sectors through tax incentives has positive potential for economic growth, but its impact must be considered as a whole to achieve sustainable public welfare. Although administrative incentives improve tax compliance, income tax reduction can promote national economic growth.